Leadership and empowering behavior: understandings of nurse managers in Primary Health Care - dos Santos, Lucas Cardoso [UNESP]; Silva, Fernanda Marques [UNESP]; da Silva Domingos, Thiago; Andrade, Juliane; Spiri, Wilza Carla [UNESP] (Acta Paulista de Enfermagem, 2023)
Objective: To understand the empowering behavior of nurses in their management practice in the Primary Health Care context. Methods: Exploratory qualitative study of nurse managers working in Basic Health Centers in a city in the state of São Paulo, Brazil. Semi-structured interviews were conducted for data collection and the content of interviews was fully transcribed. Data collection was ended after reaching theoretical data saturation in the seventh participant. The content analysis framework guided the organization of the qualitative corpus into themes and sub-themes. Results: As leaders, nurse managers use empowering behavior to interpret their perceptions and attitudes in order to positively influence teamwork and mediate conflicts. Staff sizing and difficulties in holding team meetings and sharing decision-making processes generate challenges that create tension in the implementation of empowering behavior. Conclusion: Aspects related to the management work of nurse leaders in Basic Health Centers are understood as empowering behavior and the challenges for its implementation are related to the organization and planning of the work process in Primary Health Care.
Liderazgo y comportamiento empoderador: percepciones de enfermeros-gerentes en la Atención Primaria de Salud
Liderança e comportamento empoderador: compreensões de enfermeiros-gerentes na Atenção Primária à Saúde
Keywords: Empowerment; Health service administration; Leadership; Nurses; Primary health care